Penerapan Metode Al-Miftah Lil Ulum Pada Pembelajaran Nahwu Di Madrasah Diniyah Nurul Hidayah Lecari Sukorejo Pasuruan - Yulia Rohmawati (CV. Satria Jaya, 2023)
The Al-Miftah Lil Ulum approach is a medium for mastering nahwu technology, because of the problem and period of time it takes to apprehend the technology of nahwu and sharaf the use of the conventional pesantren approach with the wish that scholars are capable of apprehend nahwu technology without problems to don't forget and apprehend. The formula of the hassle withinside the studies are: first approximately the usage of the Al-Miftah Lil Ulum approach on Nahwu topics at Madrasah Diniyah Nurul Hidayah Lecari Sukorejo, secondly approximately the impact of the Al-Miftah Lil Ulum approach on mastering results of nahwu in Madrasah Diniyah Nurul Hidayah Lecari Sukorejo, 0.33 approximately the benefits and drawbacks of the Al-Miftah Lil Ulum approach on nahwu mastering results at Madrasah Diniyah Nurul Hidayah Lecari Sukorejo The use of the Al-Miftah Lil Ulum Method has degrees including: the education stage, the implementation stage, and the assessment stage, As for the benefits of the use of the Al-Miftah Lil Ulum Method, college students are greater enthusiastic and captivated with collaborating in mastering, college students are greater energetic in mastering, offer many possibilities for college kids to engage among friends, the elegance surroundings is fun, and the weaknesses of the use of this approach encompass withinside the study room which permits college students to shout or shout. clapping in reaction to a hassle, then it may disrupt the attention of different college students.